The effect of peracetic acid on the corrosion and clearance efficiency of reused dialyzer - Phowichit, Suwadee; Wattanathana, Worawat; Spilles, Nuntana; Suwannasin, Saovanee; Permpoonsvat, Suntaree; Ussawawongaraya, Weerasak (Journal of the Nephrology Society of Thailand, 2022)
Background: A peracetic acid sterilant of dialyzer reuse is a practical approach in hemodialysis of renal replacement therapy. Currently, using of the commercial polyethersulfone (PES), a synthetic polymer-based dialyzer membrane, is increasingly utilized. However, a certain numbers of dialyzer reprocessing has not yet been determined as a standard guideline even the capacity of sterilized dialyzer can be affected by the corrosion of peracetic acid. Method: The physical and chemical characteristics of the PES membranes within dialyzers were evaluated using scanning electron microscope (SEM) and energy dispersive X-ray spectroscopy (EDS) in three female patients with end stage renal disease aged 50-65 years. The parameters of hemodialysis efficiency were also examined. Fifteen dialyzers were allocated into the following two groups as 1) three of new dialyzers (the reuse number is zero) and 2) reuse of dialyzers undergo the number of reuses increases as 1, 5, 10, and 15 times (three dialyzers for each sub-group), respectively. Results: This study showed no significant difference of the efficiency as urea reduction rate (URR), dialysis adequacy (Kt/V), and normalized protein catabolic rate (nPCR) between two groups of the patients using reused dialyzers. The result suggested that the PES membrane’s performance could be reused about 15 times. Visualization of the microstructure within the membranes was further investigated using a scanning electron microscope (SEM). The inner and outer surface areas of membranes upon the number of times for dialyzers reusable up to 10 and 15 times were corroded by peracetic acid as demonstrated by the membrane leakage and smaller membrane pore sizes, respectively. Additional evidence for the accumulation of peracetic acid leading to a destruction of the membrane structure was confirmed by energy dispersive X-ray spectroscopy (EDS). The EDS demonstrated high sulfur atoms in the inner surface area related with increased numbers of reused dialyzers. The interaction between the dialyzer membrane and peracetic acid activated many negatively charged ions absorption resulting in the membrane fouling. Conclusion: The number of PES dialyzer reuses can be performed for 10 times since the structure of dialysis membrane do not change in their element compositions and structures with a peracetic acid sterilant.